The Effect of Rape Myth Endorsement on Police Response to Sexual Assault Survivors - Garza, Alondra D. (Violence against women, 2021)
The current study used a purposive sample of 517 surveys administered to police officers at one of the five largest and most diverse U.S. cities to assess police adherence to rape myths, while considering demographic, occupational, and neurocognitive predictors. This study also examined rape myth endorsement and self-reported levels of preparedness in responding to sexual assault calls for service. Officer sex and impulsivity were significant predictors of rape myth endorsement. In addition, rape myth endorsement decreased preparedness, whereas prior specialized sexual assault training increased preparedness. Implications for policy, practice, and future research are discussed.